2012
DOI: 10.1245/s10434-012-2612-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analysis of Phase III Trials Evaluating [99mTc]Tilmanocept and Vital Blue Dye for Identification of Sentinel Lymph Nodes in Clinically Node-Negative Cutaneous Melanoma

Abstract: Background[99mTc]Tilmanocept is a CD206 receptor-targeted radiopharmaceutical designed for sentinel lymph node (SLN) identification. Two nearly identical nonrandomized phase III trials compared [99mTc]tilmanocept to vital blue dye.MethodsPatients received [99mTc]tilmanocept and blue dye. SLNs identified intraoperatively as radioactive and/or blue were excised and histologically examined. The primary end point, concordance, was the proportion of blue nodes detected by [99mTc]tilmanocept; 90 % concordance was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 18 publications
(22 reference statements)
5
92
0
4
Order By: Relevance
“…Melanoma was identified in the SLNs of 22.1% of patients. 99m Tc-tilmanocept identified more SLNs in more patients and identified more melanoma-containing nodes than VBD, with no serious adverse events attributed to 99m Tc-tilmanocept (24). A similar phase III study for SLN mapping was performed on breast cancer patients.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Melanoma was identified in the SLNs of 22.1% of patients. 99m Tc-tilmanocept identified more SLNs in more patients and identified more melanoma-containing nodes than VBD, with no serious adverse events attributed to 99m Tc-tilmanocept (24). A similar phase III study for SLN mapping was performed on breast cancer patients.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…In March 2013, the FDA approved a new agent for locating lymph nodes in patients with breast cancer or melanoma who are undergoing surgery to remove sentinel lymph nodes. The agent, technetium Tc 99m tilmanocept (Lymphoseek), is a radioactive diagnostic imaging agent that was shown in two clinical trials to locate more sentinel lymph nodes in more patients compared with vital blue dye (156,157). Further, technetium Tc 99m tilmanocept identified more sentinel lymph nodes that were subsequently shown by routine pathology to contain cancer cells.…”
Section: Mapping Cancer's Escape Routementioning
confidence: 99%
“…6 Technetium-99m-labeled tilmanocept, 7 also known as [ 99m Tc]-diethylenetriaminepentaacetic acid (DTPA)-mannosyldextran, 8 is a receptor-targeted radiopharmaceutical designed for SLN detection. Using an "instant kit" formulation 9 with the tradename Lymphoseek, a series of phase 1, 10,11 phase 2, 12 and phase 3 13,14 clinical trials, using intradermal, subareolar, and periturmoral administrations, demonstrated rapid SLN accumulation, high SLN retention, high concordance with vital blue dye, and no adverse events related to the radiopharmaceutical. Technetium-99m-labeled tilmanocept was approved for clinical use by the U.S. Food and Drug Administration in March 2013.…”
Section: Introductionmentioning
confidence: 99%